Svetozar Miletić’s Slovak Enthusiasms - Kuzmanović, Nebojša (Napredak, 2026)
The author points to the ties between Svetozar Miletić, throughout the years of his intense political activities, and other non-Hungarian nations from the Hungarian state area, with a special emphasis on Slovaks. Trying to show the permanence of these ties, the author points both to the significant biographical data from Mi letić’s life and to important political moments when the historical scene witnessed the appearance of nationally conscious Slovaks, Miletić’s friends, associates, as well as those who personally chose death to prove their loyalty to common Slavic struggle for national emancipation. The most eminent figure of the Slovak national revival, Ľudovít Štúr, is in the research focus since he had a crucial influence on the political formation of the future pivotal figure of Serbia/Vojvodina.